1996
DOI: 10.1002/(sici)1097-0320(19960901)25:1<14::aid-cyto2>3.0.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

DiOC2(3) is not a substrate for multidrug resistance protein (MRP)-mediated drug efflux

Abstract: Multidrug resistance (MDR) is often related to expression of P‐glycoprotein (Pgp) or Multidrug Resistance Protein (MRP). Pgp‐mediated MDR can be evaluated by determining cellular retention of fluorescent substrates by flow cytometry. This study determined if agents used to evaluate Pgp function also can be used to evaluate MRP function. Cellular retention of doxorubicin (Dox), Rhodamine‐123 (Rh‐123), and 3,3′‐diethyloxacarbocyanine iodide (DiOC2(3)) were studied in MRP‐expressing cell lines (HL60/Adr and HT108… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(33 citation statements)
references
References 22 publications
1
31
0
1
Order By: Relevance
“…Rhodamine is a better substrate for Pgp than MRP1, but the rhodamine efflux assay with a long (2 h) efflux is a sensitive method to detect both Pgp-and MRP1-mediated efflux. 19,24,25 Comparison of H33342 and rhodamine efflux may provide another functional assay for discriminating Pgp from MRP1.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Rhodamine is a better substrate for Pgp than MRP1, but the rhodamine efflux assay with a long (2 h) efflux is a sensitive method to detect both Pgp-and MRP1-mediated efflux. 19,24,25 Comparison of H33342 and rhodamine efflux may provide another functional assay for discriminating Pgp from MRP1.…”
Section: Discussionmentioning
confidence: 99%
“…The adherent Pgp expressing ovarian carcinoma cell line A2780/dox5 16,17 and the leukemia cell line HL60/ADR [18][19][20] displaying the MRP1 phenotype and their parent cell lines A2780/WT and HL60/WT were cultured in Iscove's medium (Life Technologies, Paisley, UK) supplemented with 10% heatinactivated fetal calf serum (FCS; Hyclone, Logan, UT, USA), 2 mM glutamine and 100 IU/ml penicillin, at 37°C in a humidified atmosphere with 5% CO 2 . The cells were used in an exponential growth phase and all cultures were routinely checked for mycoplasma contamination.…”
Section: Cell Linesmentioning
confidence: 99%
See 1 more Smart Citation
“…59,60 Another substrate, DiOC2(3), which is a substrate of Pgp, is not a substrate of MRP1. 57 Among some of these compounds are substrates of both MRP1 and Pgp, such as calcein-AM, Rh123, DNR. Although MRP1 has been identified as an organic anion transporter and Pgp as a transporter of certain positively charged compounds, there was considerable overlap in resistance spectrum, suggesting that both proteins transport important anticancer agents in AML treatment such as the anthracyclines and etoposide.…”
Section: Mrp1 Activity In Amlmentioning
confidence: 99%
“…Measuring drug efflux from these AML blast cells using the efflux of fluorescent dyes 3, 3 0 diethyloxacarbocyanine iodide (DiOC 2 (3)) and rhodamine indicated that about two-thirds of these older patients did show efflux that could be inhibited by PSC833, and one-third of patients did not have inhibitable efflux of daunorubicin or of DiOC 2 (3). 17,39,40 The CR rate was 91% in the small number of patients studied whose cells did not efflux anthracycline-like drugs and who had received the ADE regimen. This was significantly higher than the 41% CR rate seen with the same treatment in the efflux positive patients (P ¼ 0.03).…”
mentioning
confidence: 95%